2002
DOI: 10.1094/cchem.2002.79.4.511
|View full text |Cite
|
Sign up to set email alerts
|

Stress‐Strain Analysis and Visual Observation of Wheat Kernel Breakage During Roller Milling Using Fluted Rolls

Abstract: The endosperm and bran of a wheat grain have different mechanical properties and break differently under the same stresses. Stress‐strain analysis was used to model the factors affecting wheat kernel breakage during milling using fluted rolls. The planes of principal compressive and tensile stress and the maximum shear stresses, along which the kernel is most likely to be broken, were calculated for a sharp‐to‐sharp roll disposition. With the occurrence of compressive stress in the horizontal direction and she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…These particle sizes are much larger than would be expected from First Break roller milling, for which the x is 50 typically in the range 500-1500 mm (Fang & Campbell, 2003a). This suggests that the mechanism of breakage in the SKCS is primarily compression, which tends to produce larger particles, in contrast to roller milling in which shear contributes significantly, as well as compression, the relative contributions depending on roll disposition (Fang & Campbell, 2002a,b, 2003a. The large particles also reflect the relatively large final gap of 0.89 mm between the rotor and crescent in the SKCS (Martin & Steele, 1996).…”
Section: Investigation Of the Effect Of Kernel Moisture Content On Brmentioning
confidence: 90%
“…These particle sizes are much larger than would be expected from First Break roller milling, for which the x is 50 typically in the range 500-1500 mm (Fang & Campbell, 2003a). This suggests that the mechanism of breakage in the SKCS is primarily compression, which tends to produce larger particles, in contrast to roller milling in which shear contributes significantly, as well as compression, the relative contributions depending on roll disposition (Fang & Campbell, 2002a,b, 2003a. The large particles also reflect the relatively large final gap of 0.89 mm between the rotor and crescent in the SKCS (Martin & Steele, 1996).…”
Section: Investigation Of the Effect Of Kernel Moisture Content On Brmentioning
confidence: 90%
“…A review of the literature by Fang and Campbell (2002) indicated that much research has been performed on various factors affecting first-break roller milling of wheat, including physicochemical properties of the wheat kernels and aspects of roll design and operation. However, relatively little work has addressed the effect of roll disposition on the breakage patterns of wheat kernels and the resulting particle size distribution delivered by first-break roller milling.…”
mentioning
confidence: 99%
“…The value of q 2 (x) is found by integrating the mass of outlet particles of size x created by any given inlet particle of size D, multiplied by the mass of inlet particles of size D. Assuming that only breakage not aggregation occurs, outlet particles of size x cannot be created from inlet particles of size D < x, so the integration takes place over the range of inlet particles for D P x. However, in the later papers (Fang & Campbell, 2003a, 2003b the authors corrected the limits of the integration (D = 0 instead of D = x) considering the fact that, particularly under dull-to-dull disposition, under the compressive crushing forces, it is entirely possible for a wheat kernel to break so as to produce flattened bran flake with dimensions larger than the kernel from which it came (Fang & Campbell, 2002a, 2002b. Secondly, the dimensions of the wheat kernel (D) and dimension of the broken particle (x) are measured in different ways, so they are not comparable.…”
Section: The Breakage Matrix Approachmentioning
confidence: 99%